STUDENT JASLARDA HÚJDANLÍ, ÁDEP-IKRAMLÍ QARÍM-KATNAS PAZÍYLETLERIN RAWAJLANDÍRÍW - Abdimuratov, P.S.; Seytanov, B.T. (ILIM hám JÁMIYET, 2024)
The article deals the esthetic and moral education of a person, the study of a person as the social wealth, developing and enlarging moral value of ancestors.